What is the contribution of tumor capsule thickness and tumor nucleus diameter to differential diagnosis in encapsulated variant thyroid papillary carcinomas? (Annals of Medical Research, 2023)
Aim: Capsule thickness and papillary carcinoma nuclear features are common diagnostic criteria for invasive follicular variant papillary thyroid carcinoma (IEFVPTC), non-invasive follicular thyroid neoplasm with papillary nuclear features (NIFT-P), and encapsulated papillary thyroid carcinoma (E-PTC). Our goal in this study is to evaluate these two histomorphological criteria using computerized image analysis systems and to determine whether they can serve as auxiliary criteria for distinguishing these diagnostic groups.Materials and Methods: 10 patients were selected from IEFVPTC, NIFT-P, and E-PTC diagnostic groups. Slides containing the largest tumor diameter were scanned and digitized. Using computerized image analysis systems, tumor capsule thickness was measured from 4 areas of 4 equal quadrants, and the average tumor capsule thickness (TCT) was determined. Furthermore, from these 4 equal quadrants, the nucleus diameter of 10 clearly distinguishable cells was measured to determine the average tumor cell nucleus diameter (ND).Results: TCT and ND histomorphological criteria were statistically significant among the diagnostic groups. For IFVPTC diagnosis, both TCT and ND were found to be significant diagnostic tools. We demonstrated that ND can easily be used as a diagnostic tool for NIFT-P, whereas more caution is required for TCT.Conclusion: Differentiating papillary nuclear feature-containing follicular variant thyroid papillary carcinomas is challenging. In this study with a limited number of patients, we demonstrated that the TCT and ND criteria can, to some extent, contribute to differential diagnosis between diagnostic groups. Future studies with larger patient groups and more advanced computerized image analysis programs will yield more promising results.
Keywords: Computerized image analysis; Tumor capsule thickness; Tumor cell diameter; Encapsulated variant; Papillary thyroid carcinomas